Sistem Informasi manajemen Aset Di PT.XYZ Menggunakana Metode Jumlah Angka Tahun - Yuliani Dwi Utami; Tacbir Hendro Pudjiantoro (Prosiding SISFOTEK, 2020)
PT.Xyz is a company engaged in the field of design and manufacturing in improving the company, the activities carried out in PT.Xyz, asset management is still not good. The maintenance process at PT. Xyz is done conventionally which causes less than maximum activities carried out at the company carried out on assets that have been damaged, the process of documenting assets is also less controlled and used scattered so that it is difficult to use information on assets that have been done before. Besides the process of filing damage also occurs because the delay requires jawak and a long time does not correspond to the time that must be determined by the officer. With the existence of asset management at PT. Xyz can help those associated with the company. The output from this research is expected to produce a system that can help companies in managing maintenance and filing damage.